2004
DOI: 10.1023/b:caco.0000043430.32410.69
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Among Lesbians, Gays, and Bisexuals: How Serious a Problem? (United States)

Abstract: Our study provides the strongest evidence to date that lesbians, bisexual females, and gay men had significantly higher cigarette smoking prevalence rates than their heterosexual counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
132
6
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(153 citation statements)
references
References 25 publications
13
132
6
2
Order By: Relevance
“…These results are consistent with observations by Tang et al 4 and remarkably similar to those reported by McKirnan et al 13 but they stand in contrast to those from a school-based survey that found no difference in smoking at least weekly among adolescent boys who self-identify as heterosexual versus gay or bisexual. 9 The reasons underlying this inconsistency are unclear but may reflect differences among studies in the definition and selfidentification of sexual minority status, or in the distribution of participants_ age, race-ethnicity, or indicators of socio-economic status.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with observations by Tang et al 4 and remarkably similar to those reported by McKirnan et al 13 but they stand in contrast to those from a school-based survey that found no difference in smoking at least weekly among adolescent boys who self-identify as heterosexual versus gay or bisexual. 9 The reasons underlying this inconsistency are unclear but may reflect differences among studies in the definition and selfidentification of sexual minority status, or in the distribution of participants_ age, race-ethnicity, or indicators of socio-economic status.…”
Section: Discussionsupporting
confidence: 92%
“…3 A population-based survey of lesbian, gay and bisexual adults in California found that smoking was inversely associated with age, education level, income, and white (non-Hispanic) race-ethnicity. 4 Another study from California reported similar associations with age and education level. 11 Most recently, McKirnan et al compared a convenience sample of MSM in Illinois (37.5% smokers) to local National Health Interview Survey respondents (28.4% smokers); 13 younger age and lesser education were significantly associated with current smoking among MSM while, in contrast, age was not significantly associated with men in the general population sample.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In Phase 1 of the cultural adaptation process, several methods are used to identify the changes to the EBT that are necessary to achieve congruency with the target population. Both quantitative and qualitative data collection from the target population are used to help guide changes in the intervention in terms of surface structure (matching Tang et al (2005). y Binson et al (1995).…”
Section: Cultural Adaptation Of Evidenced-based Treatments For Speciamentioning
confidence: 99%